"We Palestinian Refugees" – Heritage Rites and/as the Clothing of Bare Life: Reconfiguring Paradox, Obligation, and Imperative in Palestinian Refugee Camps in Jordan. (15th September 2016) - Butler, Beverley; Al-Nammari, Fatima
Abstract : Our joint research addresses the complex role of heritage in selected Palestinian refugee camps in Jordan. Informed by the 'We Refugee' theses of Arendt (1943) and Agamben (1995) we see these 'heritage ethnographies' as a means to explore the paradoxes confronted by refugees as subject to both a 'bio-political rites of passage' that consigns them to 'spaces of exception' as 'homo sacre' and 'bare life' and as simultaneously obligated to the imperative of being the 'vanguard of their people'. Our interest is in the 'lived experiences' of refugee communities vis-à-vis their perspectives and reflections on heritage which we argue characterise a potent 'popular heritage rites'. We see these 'heritage rites' as activated heritage forms and powerful ritual acts of communion, magical thinking and wish-fulfilment that create new 'factness' and 'realities' on the ground. Thus articulated through objects (domestic-personal mementoes and souvenirs) connecting people to the Palestinian 'lost homeland' as cosmic centre/axis mundi, or via public art/ murals and as sensoriums synonymous with the preparation and ingestion of traditional food. We explore how not only traditional performances of dabke dancing but new media of rap and film-making form a fundamental part of this complex context. The Palestinian refugee voices cited in this paper see the 'thobe' - embroidered Palestinian dress - as best encompassing their understanding of heritage, similarly 'we/us', as heritage critics and contemporary archaeologists, should embrace a paradigm shift that re-situates heritage within a theory of subjectivity and recognise the efficacy of popular heritage rites to 'clothe' 'bare life' and thus to empower persons not just in the future but in the present, and thereby take on the complexities and paradoxes that being human means especially in conditions of extremis.